Impact of routine screening on detection, severity and outcome of pulmonary arterial hypertension in systemic sclerosis. (14th October 2021) - Fayed, H; Schreiber, B E; Denton, C P; Coghlan, J G; ,
Abstract: Introduction: It has been reported that up to 20% of systemic sclerosis (SSc) patients can be asymptomatic at the time of pulmonary arterial hypertension (PAH) diagnosis. The significant prevalence rate, lack of symptoms and high morbidity and mortality from SSc-PAH as well as the potential benefit from early intervention with the more widely available therapeutic options provide a strong rationale for active screening programs. The DETECT algorithm was developed in 2013 from a large prospective and multicentre study in SSc patients with higher risk of PAH. The objective of this study was to examine the impact of a screening program on the early detection of SSc-PAH. We looked at serial patients diagnosed with SSc associated PAH (SSC-PAH) in a large national pulmonary hypertension referral centre. Patients and methods: All newly diagnosed adult patients with SSc-PAH prospectively enrolled in a large national pulmonary hypertension referral centre. The current study included newly diagnosed patients between January 2006 and January 2018. Results: Three-hundred and five patients were diagnosed with SSc-PAH in our centre between 2006 and 2018. Of these, 164 patients were diagnosed before 2013 (January 2006 - December 2012) and 141 after 2013 (January 2013 - January 2018). Demographics were similar at presentation between the two groups. The non-invasive (WHO-FC, 6-MWD and NT-proBNP) and haemodynamic measurements (RAP, CI and SvO2) were used to calculate the ESC guidelines risk score. It was noted that higher proportion of patients in the post-2013 were in the higher risk categories than the pre 213 group (84.4% vs. 78%) but this was not found to be statistically significant (p value 0.356). There was no statistically significant difference in survival between the two groups (Post 2013 group, 1-, 3- year and 5-year survival was 87.9%, 60.4% and 52.1%, respectively and pre-2013 group 1-, 3- year and 5-year survival 89.6%, 65.2% and 49%, respectively) with a log rank p value of 0.869. Applying Cox regression analysis of proportional hazard and adjusting for ESC risk score at baseline, predicted survival was not found to be statistically different between the two groups. The ESC risk category at baseline was a highly significant predictor of survival as expected. Conclusion: There remains a strong rationale for active screening for PAH in SSc patients which has a poor prognosis despite advances in therapeutic strategies. However, the current screening programme does not seem to have resulted in significantly earlier detection in this cohort. It would be important to analyse other patient populations in order to understand the impact of screening programmes. The current screening programs limitations may explain why we have not been able to detect more patients in the lower risk categories. Further development of these programs in order to overcome their shortfalls is direly needed. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): National Health ServiceRoyal Free NHS Trust